THE INFLUENCE OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. BANK NANO SYARIAH BANDUNG BRANCH OFFICE - Ramdhani, Dahlan; Ridwan, Nurul Haq (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research was conducted at PT. Bank Nano Syariah Bandung Branch. The purpose of this research is to find out how much influence Motivation and Job Satisfaction contribute to employee performance, both partially and simultaneously. The research methods used in this research are descriptive methods and associative methods. In this research, the unit of analysis is the individual, namely the permanent employee of PT. Bank Nano Syariah Bandung branch. The sample in this study consisted of 36 respondents. Method The sampling technique used is saturated nonprobability sampling. The analysis method uses multiple linear regression analysis. The research instrument consists of a questionnaire, validity test and reliability test. Based on the research results, it shows that there is an influence both partially and simultaneously on exogenous variables (Motivation and Job Satisfaction) on endogenous variables (Employee Performance). The implication of this research is that it is very important to improve motivation, the better the motivation of employees, the more employee performance will increase, and job satisfaction is very important to increase if the more satisfied employees are working at PT. Bank Nano Syariah, employee performance will increase.